2021
DOI: 10.3390/ijerph18052663
|View full text |Cite
|
Sign up to set email alerts
|

Bridging or Bonding: An Organizational Framework for Studying Social Capital in Kindergartens

Abstract: The article develops our understanding of social capital by analyzing social capital as an organizational phenomenon. The analysis is based on qualitative data consisting of interviews and documents obtained from six different kindergartens in Norway. Kindergartens are used as a “prism” through which we can understand how social capital is formed—and the mechanisms that shape the development of various forms of networks within welfare organizations. More specifically we look at drop-in kindergartens. The speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Firstly, it integrates social capital and DC theories, providing a novel theoretical perspective for understanding the relationship between SSC and firm PGI. Notably, this study uncovers an implicit connection between social capital theory and DC theory, exploring how the practices of SSC, as proposed in social capital theory [130], simultaneously enhance manufacturing enterprise capabilities and motivation, as suggested by DC theory [68,128]. Such integration fosters CSC and RSC, facilitating the sharing of green knowledge among manufacturing enterprises.…”
Section: Theoretical Contributionsmentioning
confidence: 90%
“…Firstly, it integrates social capital and DC theories, providing a novel theoretical perspective for understanding the relationship between SSC and firm PGI. Notably, this study uncovers an implicit connection between social capital theory and DC theory, exploring how the practices of SSC, as proposed in social capital theory [130], simultaneously enhance manufacturing enterprise capabilities and motivation, as suggested by DC theory [68,128]. Such integration fosters CSC and RSC, facilitating the sharing of green knowledge among manufacturing enterprises.…”
Section: Theoretical Contributionsmentioning
confidence: 90%
“…Distinguishing these types of social capital is crucial in nutrition research because they can have varying effects on dietary intake (15). For instance, a study conducted in India found that bridging social capital, expressed as household connections with development-oriented community-based organizations, was positively associated with child nutrition, while bonding capital had the opposite effect (16). This disparity may be attributed to the fact that while bonding social capital can offer substantial support, its "inward" nature tends to reinforce traditional norms and habits (17).…”
Section: Introductionmentioning
confidence: 99%